Impact behaviour of omega stiffened composite panels. (February 2016) - Riccio, A.; Ricchiuto, R.; Saputo, S.; Raimondo, A.; Caputo, F.; Antonucci, V.; Lopresto, V.
Abstract: The mechanical response of reinforced composite structures under impact loads is particularly challenging owing to the rising of multiple and simultaneous failure phenomena. Indeed, low velocity impacts may produce intra-laminar damages, like fibre breakage and matrix cracking, and inter-laminar damages, such as delaminations and skin-stringer debonding. As already remarked, these failure phenomena often take place simultaneously, leading to a significant reduction in strength and stability of the composite components. In this paper, the behaviour of stiffened composite panels, with omega shaped stringers, under low velocity impacts is numerically investigated by means of non-linear explicit FEM analyses. Different impact energy levels are considered and correlation with experimental data is provided, in terms of impact force, displacement and energy. A sensitivity analysis has been performed to investigate the influence of numerical models' approximations on the accuracy of the obtained numerical results. Models with an increasing level of damage simulation details have been adopted to study the effects of combined and separated intra-laminar and inter-laminar failures providing an interesting insight on the modelling requirements for an accurate simulation of the investigated phenomena.